ANALISIS KOMPARATIF PEMBERIAN KREDIT PKBL (PROGRAM KEMITRAAN DAN BINA LINGKUNGAN) TERHADAP PRODUKSI PEMBUDIDAYA KERAMBA IKAN NILA (Oreochromes sp) DI DESA SUNGAI ULAR KECAMATAN SECANGGANG KABUPATEN LANGKAT - Asrizal Efendy Nasution; Yusniar Lubis (JURNAL AGRICA, 2017)
This research purpose is analysed production increasing of cage's cultivication Nila fishes before and after accept PKBL'S credit and how much the PKBL credit application impact to productions level step-up of cage's cultivication Nila fishes at Sungai Ular village. This method is utilized production logistic of Cobb Douglass, statistical examination to be done by use of bifilar linear regression, t partial, t distinctive two average costs, f test and determinant coefficient test. The utilized data is cultivication'.s production before and after accept PKBL 'S credit which is year 2011 and 2012. Determinant coefficient in 2011 is about 0,972 and 0,975 in 2012. T test distinctive two average cost point out to assess t computing 12, 789 < t table 4,25 that is mean that there is distinctive between average cage's production before and after accept PKBL'S credit where cage's cultivication production Nila fishes increases after accept PKBL 'S credit.